2001
DOI: 10.1681/asn.v12112253
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Autoregulation of Renal Blood Flow in Conscious Rats

Abstract: Abstract. Response of renal vasculature to changes in renal perfusion pressure (RPP) involves mechanisms with different frequency characteristics. Autoregulation of renal blood flow is mediated by a rapid myogenic response and a slower tubuloglomerular feedback mechanism. In 25 male conscious rats, ramp-shaped changes in RPP were induced to quantify dynamic properties of autoregulation. Decremental RPP ramps immediately followed by incremental ramps were made for four different rates of change, ranging from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It was demonstrated that with the influence of TGF, the afferent arteriole has a lower diameter and a further decrease in afferent arteriole diameter due to MR being markedly enhanced [ 14 , 17 , 21 ]. MR, in combination with TGF, is needed for an optimal RBF autoregulation and MR with its higher frequency acts as a dampening system, whereas TGF with its lower frequency modulates MR and represents a fine-tuning stabilization of renal function [ 22 ].…”
Section: Autoregulationmentioning
confidence: 99%
“…It was demonstrated that with the influence of TGF, the afferent arteriole has a lower diameter and a further decrease in afferent arteriole diameter due to MR being markedly enhanced [ 14 , 17 , 21 ]. MR, in combination with TGF, is needed for an optimal RBF autoregulation and MR with its higher frequency acts as a dampening system, whereas TGF with its lower frequency modulates MR and represents a fine-tuning stabilization of renal function [ 22 ].…”
Section: Autoregulationmentioning
confidence: 99%